Pendampingan Teknologi Bak Sampah Otomatis untuk Meningkatkan Kebersihan Lingkungan di Kantor Desa Gelora - Sandi, Arnila Sandi; Yahya, Yahya; Dewi P, Intan Komala; Yudha, Pramandane Setya; Paizurrohman, Moh. Doni (Universitas Hamzanwadi, 2024)
A clean and confortable environment can create quality human resources. Environmental cleanliness is ansituation and condition that has a good place and is not polluted by dirt and is beautiful to look at. One of the causes of major social conflict in a country is the waste problem. Because the waste problem never ends along with the development of the population in the area. For example in Gelora village, Sikur sub-district, East Lombok, in this area assistance is being provided for making automatic waste bins which will be implemented at the Gelora Village office. In the current technological era, this is very possible to happen, but it can be used as a lesson to create an innovation that can help alleviate existing problems. Together with the authorities, the community and the Hamzanwadi University Village Development KKN Internship team, we provided assitance in making automatic trash bins with an Internet of Things system. Several components used include Arduino Uno, Servo, and Ultrasonic sensor. This assistance aims to increase and encourage public and staff awareness in the Gelora Village office environment regarding environmental cleanliness by utilizing technology. So it can produce a comfortable, clean and healthy environment